KAJIAN HUKUM INTERNASIONAL TERHADAP PERUBAHAN STATUS PALESTINA DARI ENTITAS PEMANTAU NON-ANGGOTA MENJADI NEGARA PEMANTAU NON-ANGGOTA - Samosir, Christy Oktaviani; Pasek Diantha, I Made; Mahartayasa, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
The status of Palestine has changed from a non-member observer entity into a non-member observer state of the United Nations at 29th November 2012. This decision made the relationship among the states world was uneasy. As known, that until this day, Palestine and Israel still make the war happen because Gaza region. This decision wasn’t received by Israel, Israel declared that this decision was the beginning of the loss of peace between these states. The transformation of Palestine status automatically offers the new rights for Palestine, including right to votes for their freeedom from the war.
Keywords: international law, a non-member observer entity, a non-member observer state, rights transformation